The effect of macroeconomics variables on sustainable developments in Malaysia / Farahana Sahibollah @ Sarip - Sahibollah @ Sarip, Farahana (2018)
Adjusted Net Saving (ANS) rate has been introduced by the World Bank during 1990s as an alternative indicator to measure sustainable development. The interesting features are the depreciation or depletion of natural capital is included in the aggregate indicators of net national output. Since its conception, most governments around the world have adopted sustainable development as their national objective. For a developing country like Malaysia, the national goal to achieve sustainability has indeed becoming key element. The aim of this research is to investigate the relationship of the macroeconomics variables and adjusted net saving towards sustainable developments in Malaysia. There are four variables used in this study which are financial development, income per capita; inflation and mineral depletion. These independent variables might have effect on sustainable development, as proxied by Adjusted Net Saving in Malaysia. The tests that will be using in this study are pooled ordinary least square (POLS) method. This research attempted to analyse the factors that might have effect on sustainable development in Malaysia. By doing this research, it help to provide firmed macroeconomic policy should be carefully designed by policymaker in order to ensure a sustainable development in both economic and environmental aspects, especially for a country like Malaysia. In this study, the finding for the variable income per capita, inflation and mineral depletion are positive while financial development are negative relationship with adjusted net saving.